AB0411 Rapid Reduction of Antibodies and Improvement of Disease Activity by Immunoadsorption in Chinese Patients with Severe Systemic Lupus Erythematosus. (15th July 2016) - Huang, J.; Song, G.; Yin, Z.; He, W.; Zhang, L.; Kong, W.; Ye, Z.
Abstract : Background: Immunoadsorption (IAS) has been used to treat patients with SLE for many years. Efficacy was proved for case report or series with SLE after IAS treatment, while case-control studies are so far lacking. Objectives: We aim to evaluate the efficacy and safety of IAS as an addition to aggressive immunosuppressive treatment in Chinese SLE patients with severe disease activity. Methods: Patients with SLE disease activity index 2000 (SLEDAI 2k) >15 were enrolled. The number of patients in IAS group and non-IAS group was 52, including 22 with lupus nephritis (LN), 10 with severe thrombocytopenia (<10 platelets/×10 9 /l), 10 with neuropsychiatric lupus and 10 with a large pericardial effusion, respectively. Observation study was performed for every individual in either group for 3 months. Corticosteroid pulse therapy (CSPT, intravenous methylprednisolone 250 mg/day for 3 days) was given to each patient consecutively, followed by a daily oral dose of 1 mg/kg bodyweight of corticosteroid. Corticosteroid were tapered by 10% every 1∼2 weeks after 4 weeks. IAS was initiated on the second day of CSPT. Other immunosuppressant included intravenous cyclophosphamide pulse therapy (IVCY, targeting 0.5 g/m 2 body surface area) every 2 weeks for 3 months. IVCY was initiated after 3 days' of CSPT. Results: In total 52 SLE patients, the improvement of C3 level, dsDNA and AnuA titer after treatment at different visits compared with baseline was discovered in both groups, while the overall changes of these markers in IAS group were all more significant than those in non-IAS group. Similar results were observed in subgroup analysis. SLEDAI score dropped significantly after 1 week of treatment both in IAS group (from 24.46±4.14 to 12.65±3.85, p=1.13×10 –27 ) and non-IAS group (from 24.46±4.07 to 14.67±3.42, p=5.41×10 –24 ), while the significance was more prominent in IAS group (p=0.004). The dosage of steroids used at 3 months was significantly lower in IAS group (13.46±4.12mg) than that in non-IAS group (15.10±3.77mg) (p=0.037). No severe side effect occurred in our study. Conclusions: This is the first report of the application of phenylalanine immunoadsorption to treating patients with SLE in China. In combination with corticosteroid therapy and immunosuppressant, IAS would appear to be an effective and safe treatment optimal for SLE, without consideration of its high cost. References: Stummvoll GH. Immunoadsorption (IAS) for systemic lupus erythematosus. Lupus. 2011; 20(2):115–9. [PubMed: 21303827] Tan EM, Cohen AS, Fries JF, Masi AT, McShane DJ, Rothfield NF, et al. The 1982 revised criteria for the classification of systemic lupus erythematosus. Arthritis Rheum 1982; 25:1271–7. [PubMed: 7138600] Hochberg MC. Updating the American College of Rheumatology revised criteria for the classification of systemic lupus erythematosus. Arthritis Rheum. 1997; 40:1725. [PubMed: 9324032] Petri M, Orbai AM, Alarcόn GS, Gordon C, Merrill JT, Fortin PR, et al. Derivation and validation of the Systemic Lupus International Collaborating Clinics classification criteria for systemic lupus erythematosus. Arthritis Rheum. 2012 Aug;64(8):2677–86. [PubMed: 22553077] Acknowledgement: We thank the nursing team of the apheresis unit for accurate and friendly support. Disclosure of Interest: None declared